2022
DOI: 10.1093/infdis/jiac199
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults Mount Less Durable Humoral Responses to Two Doses of COVID-19 mRNA Vaccine but Strong Initial Responses to a Third Dose

Abstract: Background Third COVID-19 vaccine doses are broadly recommended, but immunogenicity data remain limited, particularly in older adults. Methods We measured circulating antibodies against the SARS-CoV-2 spike protein receptor-binding domain, ACE2 displacement, and virus neutralization against ancestral and Omicron (BA.1) strains from pre-vaccine up to one month following the third dose, in 151 adults aged 24-98 years who receiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 47 publications
5
41
2
Order By: Relevance
“…The authors concluded that such events were rare (<0.1% of cases during the brief window of analysis) and more likely to occur among unvaccinated individuals, but further evaluation of the data indicates a majority of reinfection cases were due to BA.2 following BA.1. Moreover, given that the present case participant was one of only 151 enrolees of an observational COVID-19 vaccine study (25,26), our results suggest that the risk of serial infection with Omicron subvariants may be greater than current assumptions based on low reinfection rates. We note however that the participant's status as a frontline healthcare worker may have resulted in an increased risk of exposure and (re-)infection over the general population.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The authors concluded that such events were rare (<0.1% of cases during the brief window of analysis) and more likely to occur among unvaccinated individuals, but further evaluation of the data indicates a majority of reinfection cases were due to BA.2 following BA.1. Moreover, given that the present case participant was one of only 151 enrolees of an observational COVID-19 vaccine study (25,26), our results suggest that the risk of serial infection with Omicron subvariants may be greater than current assumptions based on low reinfection rates. We note however that the participant's status as a frontline healthcare worker may have resulted in an increased risk of exposure and (re-)infection over the general population.…”
Section: Discussionmentioning
confidence: 71%
“…The observation that average humoral responses to three-dose vaccination failed to protect against Omicron BA.1 infection is consistent with the extremely high rates of community transmission observed in many regions during the recent Omicron-driven pandemic waves. Given that third doses substantially boost humoral responses in individuals of all ages (29)(30)(31)(32), the risk of Omicron infection is likely to be higher among individuals who have received fewer than three doses (18,33) and is likely to increase with time following vaccination due to natural declines in antibody responses (26,(34)(35)(36)(37). Additional studies are needed to assess these factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our retrospective cohort analysis revealed a consistent decline in the estimated vaccine effectiveness with age. Although we attribute this decline to the assumption that there are more people with comorbidities among the elderly vaccinated compared to the unvaccinated of the same age, we do not rule out that in the elderly, vaccine-induced protective immunity can weaken more quickly because their antibody levels might decrease faster, as shown in a number of publications for different vaccines [ 43 , 44 , 45 , 46 ]. After vaccination with BNT162b2, the level of antiviral IgG antibodies decreased faster in older vaccine recipients (≥50).…”
Section: Discussionmentioning
confidence: 91%
“…26 They may benefit enormously from active vaccination, 27 which can stimulate the production of neutralizing antibodies and promote viral clearance. Recent evidence demonstrates the safety and good tolerance of vaccines in the elderly with primary conditions 28 and a necessity of vaccinating the elderly 29 . In addition, the overall NAN median time of 15 days suggests that it is necessary to quarantine the infected people for at least 15 days in order to minimize the possibility of transmission, which may be prolonged for elderly people with primary conditions.…”
Section: Discussionmentioning
confidence: 99%